Presenting of Special Express Mail’s Production and Revenue Data of 2022 Using Descriptive Statistics - Antonio Vaticano Lekahena; Esther Ria Matulessy (International Journal Labs, 2023)
The author wants to know the results of a descriptive statistical analysis based on income and production of postal shipments in 2021 and 2022 from 3 types of services including Special Express Mail, Special Express Packages, and Corporate. Descriptive analysis is a form of research data analysis to test the generalization of research results based on one sample. There are three main things contained in statistics, namely; data, treatment of data in the form of collection, processing/analysis, analysis and drawing conclusions, and numbers. Descriptive statistics is a part of statistics that discusses how to collect and present data so that it is easy to understand and provides useful information. The conclusions that can be drawn from the results of the descriptive statistical analysis of each service are; the highest Outoging production in 2022 comes from Special Express Packages with a total production of 14,095 units or 97% of the total production, the highest outog delivery revenue in 2022 comes from Special Express Packages with a total revenue of Rp. 1.138.614.776.- or 97% of the total revenue, the highest incoming shipping production in 2022 comes from Special Express Packages with a total production of 21,235 units or 96% of the total production, the highest incoming delivery income in 2022 comes from Special Express Packages with total income of Rp. 2.650.031.160,- or 88% of the total income.